Cephalopod‐Inspired Design of Photomechanically Modulated Display Systems for On‐Demand Fluorescent Patterning. Issue 4 (26th November 2021) - Shi, Huihui; Wu, Shuangshuang; Si, Muqing; Wei, Shuxin; Lin, Guoqing; Liu, Hao; Xie, Weiping; Lu, Wei; Chen, Tao
Abstract: Cephalopods can display variable body color/patterns upon environmental stimulation via bioelectricity‐controlled muscle contraction/expansion of skin chromatophores. However, it remains challenging to produce artificial display analogs that exhibit reversible and rapid switching between multiple expected luminescent patterns, although such systems are very appealing for many practical uses (e.g., data encryption). Inspired by the bioelectromechanical display tactic of cephalopods, in this work, a conceptually new photomechanically modulated fluorescent system that enables on‐demand display of fluorescent patterns via a cascading stimulation−mechanical movement−optical output conduction mechanism is presented. Specifically, this biomimetic system comprises a customizable hollow display panel and a bottom‐tethered photothermally responsive fluorescent actuator. Under NIR light, the photomechanically bending movements of the fluorescent actuator will immediately cover the hollow window of the display panel and synchronously manifest as the display of fluorescent patterns. Owing to its desirable time‐ and light‐power‐dependent actuating behaviors, diverse fluorescent patterns/information can be dynamically and reversibly displayed by facilely controlling this single remote NIR signal. This bioinspired strategy is universal and promising for fabricating on‐demand fluorescent display platforms that combine a wide choice of fluorophores, remote control with high spatial/temporal precision, and especially single‐input multiple‐output features. Abstract : Inspired by the bioelectromechanical display mechanism of cephalopods, a conceptually new photomechanically modulated fluorescent system is developed. Its key component is an NIR‐light‐responsive fluorescent actuator with desirable time‐ and NIR light power dependent actuating behaviors. When paired with customizable display panels, on‐demand display of diverse fluorescent patterns/information can be realized by facilely controlling the single remote NIR signal.